PmtA Regulates Pyocyanin Expression and Biofilm Formation in Pseudomonas aeruginosa - Thees, Amy V.; Pietrosimone, Kathryn M.; Melchiorre, Clare K.; Marden, Jeremiah N.; Graf, Joerg; Lynes, Michael A.; Maltz-Matyschsyk, Michele (Frontiers in Microbiology, 2021)
The opportunistic pathogen Pseudomonas aeruginosa expresses a small molecular weight, cysteine-rich protein (PmtA) identified as a metallothionein (MT) protein family member. MT family proteins have been well-characterized in eukaryotes as essential for zinc and copper homeostasis, protection against oxidative stress, and ability to modify a variety of immune activities. Bacterial MTs share sequence homology, antioxidant chemistry, and heavy metal-binding capacity with eukaryotic MT, but the impact of bacterial MTs on virulence and infection have not been well-studied. In the present study, we investigated the role of PmtA in P. aeruginosa PAO1 using a PmtA-deficient strain (ΔpmtA) and assessed its role in the production of virulence factors known to be important for infection. Here we demonstrate the potent virulence factor pyocanin, which induced oxidative stress, relies on the expression of PmtA. PmtA may be protective against oxidative stress, as exogenous antioxidant can rescue pyocyanin expression. Furthermore, the expression of phzM, which encodes a pyocyanin precursor enzyme, was decreased in the ΔpmtA mutant during early stationary phase. Upregulated pmtA expression was previously detected in confluent biofilms, which are essential for chronic infection, and we observed that the ΔpmtA mutant was disrupted for biofilm formation. Since biofilms also modulate antibiotic susceptibility, we examined the ΔpmtA mutant susceptibility to antibiotics and found that the ΔpmtA mutant is more susceptible to cefepime and ciprofloxacin than the wild-type strain. Finally, we observed that the deletion of pmtA results in decreased virulence in a waxworm model compared to the wild-type strain. Taken together, our results support the conclusion that PmtA is necessary for the full virulence of P. aeruginosa and may represent a potential target for therapeutic intervention.